1996
DOI: 10.1121/1.417357
|View full text |Cite
|
Sign up to set email alerts
|

The effect of segment duration on the perceptual integration of nasals for adult and child speech

Abstract: It has been hypothesized that the acoustic properties within a temporal domain of 10 to 30 ms of boundaries between speech sounds contain significant information on the phonetic features of segments, and that these cues are perceptually integrated by the auditory system [Stevens, Phonetic Linguistics: Essays in Honor of Peter Ladefoged (Academic, London, 1985)]. The purpose of the current research was to examine the effects of stimulus duration adjacent to speech sound boundaries on the perceptual integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The inspiration for the experiments comes from by speech generation; frequency transitions are present in speech signals and are believed to be one of the fundamental features involved in word recognition (Gulick et al 1989). For example, it has been demonstrated in several experiments with frequency transitions over a short time interval, such as those found in consonant-vowel boundaries, that the 10 ms portion of the waveform prior to the stationary vowel segment contains the crucial information for proper syllable detection (Ohde and Ochs 1996). For example, it has been demonstrated in several experiments with frequency transitions over a short time interval, such as those found in consonant-vowel boundaries, that the 10 ms portion of the waveform prior to the stationary vowel segment contains the crucial information for proper syllable detection (Ohde and Ochs 1996).…”
Section: Classification With a Priori Weightsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inspiration for the experiments comes from by speech generation; frequency transitions are present in speech signals and are believed to be one of the fundamental features involved in word recognition (Gulick et al 1989). For example, it has been demonstrated in several experiments with frequency transitions over a short time interval, such as those found in consonant-vowel boundaries, that the 10 ms portion of the waveform prior to the stationary vowel segment contains the crucial information for proper syllable detection (Ohde and Ochs 1996). For example, it has been demonstrated in several experiments with frequency transitions over a short time interval, such as those found in consonant-vowel boundaries, that the 10 ms portion of the waveform prior to the stationary vowel segment contains the crucial information for proper syllable detection (Ohde and Ochs 1996).…”
Section: Classification With a Priori Weightsmentioning
confidence: 99%
“…For example, it has been demonstrated in several experiments with frequency transitions over a short time interval, such as those found in consonant-vowel boundaries, that the 10 ms portion of the waveform prior to the stationary vowel segment contains the crucial information for proper syllable detection (Ohde and Ochs 1996). For example, it has been demonstrated in several experiments with frequency transitions over a short time interval, such as those found in consonant-vowel boundaries, that the 10 ms portion of the waveform prior to the stationary vowel segment contains the crucial information for proper syllable detection (Ohde and Ochs 1996). Also, Stevens et al (1992) demonstrated the importance of the spectral changes between the consonant and vowel for use in classification.…”
Section: Classification With a Priori Weightsmentioning
confidence: 99%
“…Several acoustic properties have been shown to contribute to the perception of place of articulation in adult and child speakers' production of nasal consonants ͑Kurowski and Blumstein, 1984;Repp, 1986;Repp and Svastikula, 1988;Ohde and Perry, 1994;Ohde and Ochs, 1996͒. The most distinctive acoustic properties of consonantvowel ͑CV͒ and vowel-consonant ͑VC͒ syllables include a low-frequency murmur representing sound passing through the nose and a relatively abrupt change in amplitude and spectrum at the juncture between the consonant and the vowel.…”
Section: Introductionmentioning
confidence: 99%
“…Results from studies on nasal consonants indicate that the perceptual mechanisms involved in processing spectral change may include early integration of physiological processes mediated by short-term adaptation ͑Delgutte, 1980; Delgutte and Kiang, 1984͒ and/or late integration of cognitive processes mediated by long-term auditory memory ͑Repp, 1987; Ohde and Perry, 1994;Ohde and Ochs, 1996͒. The adaptation effect in humans may involve the murmur in CVs adapting the following vowel onset by attenuating low resonance frequencies and enhancing second and third formant transitions, where distinctive place of articulation cues are located. The acoustic metrics that have been proposed to account for the perception of spectral discontinuities in nasal consonant+ vowel syllables include relational cues residing in the spectral change between the murmur and the vowel ͑Kurowski and Blumstein, 1987;Seitz et al, 1990;Kurowski and Blumstein, 1993͒ and the relational property of the combination of separately processed murmur and vowel spectra ͑Harrington, 1994͒.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation